2019
DOI: 10.1093/rheumatology/kez556
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for varicella zoster virus in patients newly suspected of having giant cell arteritis

Abstract: Objectives There is uncertainty if varicella zoster virus (VZV) triggers GCA. This is based on discordant reports of VZV detection in GCA temporal artery biopsies. We conducted a multimodal evaluation for VZV in the inception Giant Cell Arteritis and PET Scan (GAPS) cohort. Methods Consecutive patients who underwent temporal artery biopsy for suspected GCA were clinically reviewed for active and past VZV infection and followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 11 publications
1
28
0
2
Order By: Relevance
“…Although the sensitivity of TAB may be 77% for fulfilment of the American College of Rheumatology 1990 criteria for GCA, 91 it is likely lower for the clinical diagnosis in daily clinical practice. 6 Some studies in our meta-analysis 46,68,71,[75][76][77]82 reported a subgroup of patients with TAB findings that were negative for GCA. Patients with GCA may have had TAB findings negative for GCA in other studies, but these patients were simply classified as not having GCA.…”
Section: Limitationsmentioning
confidence: 95%
See 4 more Smart Citations
“…Although the sensitivity of TAB may be 77% for fulfilment of the American College of Rheumatology 1990 criteria for GCA, 91 it is likely lower for the clinical diagnosis in daily clinical practice. 6 Some studies in our meta-analysis 46,68,71,[75][76][77]82 reported a subgroup of patients with TAB findings that were negative for GCA. Patients with GCA may have had TAB findings negative for GCA in other studies, but these patients were simply classified as not having GCA.…”
Section: Limitationsmentioning
confidence: 95%
“…Of the 1436 reports screened, 68 studies 14-17,24-87 fulfilled the selection criteria and were used for the systematic review and metaanalysis (eFigure 1 in the Supplement). These studies included 14 037 patients, of whom 4277 (30.5%) were classified as having GCA ( 16,17,[24][25][26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][59][60][61][62][66][67][68][69]72,73,[75][76][77][78][79][80][81][82][83][84]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations